Electrographic flow-guided ablation in redo patients with persistent atrial fibrillation (FLOW-AF): design and rationale - Szili-Torok, Tamas; Neuzil, Petr; Langbein, Anke; Petru, Jan; Funasako, Moritoshi; Dinshaw, Leon; Wijchers, Sip; Bhagwandien, Rohit; Rillig, Andreas; Spitzer, Stefan G; Metzner, Andreas; Kong, Melissa H; et al. (Heart rhythm O2, 2023)
BACKGROUND: Electrographic flow (EGF) mapping enables the dynamic detection of functional or active atrial fibrillation (AF) sources outside the pulmonary veins (PVs), and the presence or absence of these sources offers a novel framework for classifying and treating persistent AF patients based on the underlying pathophysiology of their AF disease. OBJECTIVE: The primary objective of the FLOW-AF trial is to evaluate the reliability of the EGF algorithm technology (Ablamap software) to identify AF sources and guide ablation therapy in patients with persistent AF. METHODS: The FLOW-AF trial (NCT04473963) is a prospective, multicenter, randomized clinical study in which patients with persistent or long-standing persistent AF who have failed prior PV isolation (PVI) undergo EGF mapping after confirmation of intact PVI. In total, 85 patients will be enrolled and stratified based on the presence or absence of EGF-identified sources. Patients with an EGF-identified source above the predetermined activity threshold of ≥26.5% will be randomized in a 1:1 fashion to PVI only vs PVI + ablation of EGF-identified extra-PV sources of AF. RESULTS: The primary safety endpoint is freedom from serious adverse events related to the procedure through 7 days following the randomization procedure; and the primary effectiveness endpoint is the successful elimination of significant sources of excitation with the target parameter the activity of the leading source. CONCLUSIONS: The FLOW-AF trial is a randomized study designed to evaluate the ability of the EGF mapping algorithm to identify patients with active extra-PV AF sources.